Nam Cao, Vũ Trọng Phụng Tuyển chọn và trích dẫn những bài phê bình - bình luận văn học... - Hà Minh Đức (TH Khánh Hòa, 1991)
Tuyển chọn và trích dẫn những bài phê bình - bình luận văn học Nam Cao, Vũ Trọng Phụng